2003
DOI: 10.1021/ja0352496
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Strength of Lectin Binding Interactions and Controlling the Amount of Lectin Clustering Using Mannose/Hydroxyl-Functionalized Dendrimers

Abstract: Protein-carbohydrate interactions play a critical role in many biological recognition events. Multivalent therapeutic agents that utilize protein-carbohydrate interactions have proven difficult to design, primarily because the fundamental requirements of protein-carbohydrate interactions are not well understood. Here, we report a systematic study of the effect on lectin binding of varying the loading of mannose surface residues on generations three through six PAMAM dendrimers. The degree of mannose functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 50 publications
11
161
2
Order By: Relevance
“…Representative examples of scaffolds for polyvalent ligands: polyacrylamide [6,7,110], ROMP [106], poly( p-phenylene ethynylene), PAMAM dendrimer first generation [111], and protein [109,112]. The protein was rendered as a molecular surface (shaded gray) with displayed ligands shown in black using Swiss PDB Viewer and deposited atomic coordinates (PDB 1V9I) [113].…”
Section: Fig 210mentioning
confidence: 99%
“…Representative examples of scaffolds for polyvalent ligands: polyacrylamide [6,7,110], ROMP [106], poly( p-phenylene ethynylene), PAMAM dendrimer first generation [111], and protein [109,112]. The protein was rendered as a molecular surface (shaded gray) with displayed ligands shown in black using Swiss PDB Viewer and deposited atomic coordinates (PDB 1V9I) [113].…”
Section: Fig 210mentioning
confidence: 99%
“…In fact, glycan structures, unsurpassed in coding capacity relative to proteins and nucleic acids, serve as signals in many bioprocesses, from cell adhesion and growth regulation to diverse transport processes (4)(5)(6)(7)(8)(9). Consequently, a wide array of synthetic products for the many roles of glycans must be prepared by diversity-oriented approaches (10)(11)(12)(13)(14)(15). The self-assembly of Janus GDs into GDSs enables analysis of trans (bridging) contacts.…”
mentioning
confidence: 99%
“…We developed new electron spin resonance and mass spectrometry methods to characterize the chemistry of heterogeneous functionalization with molecular groups, e.g., nitroxyl spin-label molecular probes, single-ring aromatics, and small carbohydrates. These structurally-characterized, functionalized templates are presently being applied as analytical probes cell-cell interactions [1].…”
Section: Co-pi -David J Singelmentioning
confidence: 99%
“…To this end we studied the polymerization which occurs when bis(oxalate) palatinate(II) anions are oxidized. We characterized the dimer, trimer, tertramer, and pentamer species containing two to five platinum atoms bound to one another in linear arrays 1 and we showed that macroscopic wires were themselves polymers of the pentameric species. 2 Optical properties and thermodynamic formation constants were reported as well.…”
mentioning
confidence: 99%